Evolução do perfil espacial de mortalidade de acidentes de trânsito no Brasil e microrregiões, 1996-2015 - Júlia Clétilei Magalhães da Silva (2020)
BACKGROUND Traffic Accidents (TA) have been a relevant external cause in the context of morbidity and mortality in Brazil, not only in the national mortality ranking, but also due to the morbidities generated based on hospitalizations resulting from hospitalizations and/or events arising from permanent or non-permanent sequels. For men, according to the IHME/GBD, TA occupy the 2nd place, while globally it occupies the 3rd position. For women this occurs respectively in 4th and 7th, both for 2017 and for 15-49 years. The mortality rate due to TA in recent decades has shown growth in the country, but with regional variability. This spatial and temporal heterogeneity can be explained by factors related to safety, health and public policies, in addition to socioeconomic development. OBJECTIVE The primary objective of this work is to produce robust estimates for mortality due to TA for small areas, broken down by gender, among the age group from 15 to 35 years. Second, to spatially and over time evaluate TA mortality rates in 4 large groups including 1996-2000, 2001-2005, 2006-2010, 2011-2015, to avoid possible random fluctuations and to verify whether or not there was spread of mortality by the micro-regions of the country. The hypothesis is that over the years, with the increase in the fleet of vehicles throughout the country, and with the increase in deaths, the latter are with a greater spatial dispersion and are strongly related to men aged 15 to 35 years. METHODS We used the James-Stein Bayesian Empirical Statistics method to produce more robust mortality due to TA and to evaluate by descriptive and spatial analyzes as to differences in the observed mortality rates due to TA. Based on these practices, it uses spatial analysis, LISA Cluster, to check possible patterns and trends of TA mortality, for men and women, aged 15 to 35 years, for micro-regions of Brazil and for 4 periods from 1996 to 2015. The data are SIM/DATASUS and IBGE. RESULTS The spatial distribution by sex shows different patterns and trends across Brazilian micro-regions. Men and women, aged 15-35 years, have distinct Mortality Rates from TA and women much lower than men. In addition, there is a spatial dispersion observed throughout the 1996-2015 series at the micro-region level especially linked to the socioeconomically less favored micro-regions and a downward trend in rates overall. Spatial heterogeneity is marked by the spread of mortality rates due to TA, so that the spot of clusters of micro-regions of high rates shows a trend moving from the South and Southeast to the Midwest and Northeast throughout the 1996-2015 series. The mortality rates due to TA in the southern and southeastern micro-regions, even numerically higher, show a drop over the five years analyzed and maintain a standard neighborhood with low mortality rates due to TA. These facts are especially more significant for women. CONTRIBUTIONS The relevance of the study is to verify how is the trend of evolution of mortality rates due to TA, by micro-region, throughout 1996-2015 in the country showing that public policies related to safety and health can help to reclaim this scenario. In addition, an important contribution is to create more robust estimates for analyzing mortality rates for small areas. In general, the drop in mortality rates from TA in most micro-regions is a warning sign that public road safety policies and more effective coercive transit measures will continue to watch over society to contain the spread and the fall scenario, especially in those socioeconomically disadvantaged places. Generating impacts on public health, the Epidemiological Transition, in this context, is also extremely important since external causes have been gaining a role at the top of the causes of death.